Hierarchical carbon coated molybdenum dioxide nanotubes as a highly active and durable electrocatalytic support for methanol oxidation. Issue 8 (1st February 2017) - Zhang, Jing-Jia; Sui, Xu-Lei; Huang, Guo-Sheng; Gu, Da-Ming; Wang, Zhen-Bo
Abstract : Hierarchical nanotubes of Pt/MoO2 @C catalyst demonstrated good catalytic activity and ultrahigh stability towards methanol electrooxidation due to the large surface area and good corrosion resistance. Abstract : Molybdenum dioxide (MoO2 ) has been adopted as an advanced auxiliary support material for its outstanding electrical properties to anchor metal nanoparticles (NPs). To overcome the drawback of MoO2 electronic conductivity, a novel hierarchical carbon coated molybdenum dioxide (MoO2 @C) nanotube built from ultra-thin nanosheets was utilized as a nanostructured support. Pt NPs were uniformly deposited onto the MoO2 @C support and a hierarchical Pt-based anode catalyst was successfully synthesized. Benefitting from several favourable features, including high exposed surface area, short diffusion distance, fast charge transfer and homogeneous Pt NPs dispersion, the Pt/MoO2 @C catalyst exhibited an improved activity along with enhanced stability for methanol electrooxidation when compared with that of the Pt/C catalyst. This novel hierarchical structure is helpful for the further applications in hydrogen evolution reaction, supercapacitors and batteries.